Current frontiers in clinical research application of MALDI imaging mass spectrometry. (June 2013) - Neubert, Patrick; Walch, Axel
Imaging mass spectrometry (IMS) is still a relatively young imaging technique that allows molecular mapping of diverse biomolecules in their natural environment. Furthermore, IMS allows for the direct correlation of tissue histology and proteomic, metabolomic or lipidomic information. In recent years, increasing efforts have been made in the development and improvement of IMS, which aid its application in clinical research. In this article, current frontiers of clinical research applications of IMS are discussed in the context of recent developments of IMS technology. Critical stages in planning and realizing clinical studies are highlighted. Finally, a selection of recent prominent examples for successful clinical applications of IMS is presented.